(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to compare the nutrient utilization,concentration of some rumen metabolites, blood urea nitrogen and somephysiological responses to water restriction in Sudan desert sheep andNubian goats. Three yearling uncastrated intact males from each species,averaging 18.37 kg (for sheep) and 13.21 kg (for goats), were randomlyallotted to four treatments in a completely randomized block design witha 2 x 2 factorial arrangement of treatments to determine the effects ofanimal species and water restriction. Both species were offered either adlibitum feed and water or water restricted to 50% of ad libitum level withad libitum feed. Animal species resulted in a significant (P<0.01) increasein dry matter intake, water intake, faecal dry matter and respiration rateand a decrease (P<0.01) in water intake: dry matter intake ratio in sheepcompared with goats. Sheep showed also higher (P<0.05) urine volumevalue than goats. Rectal temperature was not affected by animal species.Dry matter intake, faecal dry matter and urine volume decreasedinsignificantly with water restriction. However, water intake and waterintake: dry matter intake ratio decreased significantly (P<0.01) withtreatment. Rectal temperature and respiration rate values were almostsimilar at the two levels of water intake. Species x treatment interactionshowed a significant (P<0.01) increase in water intake in sheep comparedwith goats given water ad libitum. Water intake, however, decreased inboth species as a result of water restriction. Animal species induced asignificant effect on the apparent digestibility coefficients of dry matter,organic matter, crude protein, crude fibre, nitrogen free extract and totaldigestible nutrients. Ether extract digestibility did not differ betweenspecies. Goats had lower digestibility coefficients and total digestiblenutrients compared with sheep. Except for ether extract digestibility, the 233Sulafa M. H. Hassouna and Asim A. A. Lutfidigestibility coefficients of nutrients as well as total digestible nutrientsincreased with water restriction. Sheep had the highest nitrogen balancevalue. Nitrogen balance showed similar trend whether it is expressed as apercentage of nitrogen intake or digested nitrogen. Species x treatmentinteractions were not found for digestibility and nitrogen balance data.Rumen pH and ammonia nitrogen were not affected significantly byspecies. Water restriction did not induce a significant effect on rumen pHand blood urea nitrogen. A significant species and treatment effect onblood urea nitrogen and ammonia nitrogen, respectively, was recorded.